Use of whole-genome sequence data for fine mapping and genomic prediction of sea louse resistance in Atlantic salmon - Onabanjo, Olumide; Meuwissen, Theo; Aslam, Muhammad Luqman; Schmitt, Armin Otto; Dagnachew, Binyam (Frontiers in Genetics, 2024)
Sea lice (Lepeophtheirus salmonis) infestation of Atlantic salmon (Salmo salar) is a significant challenge facing aquaculture. Over the years, this parasite has developed immunity to medicinal control compounds, and non-medicinal control methods have proven to be stressful, hence the need to study the genomic architecture of salmon resistance to sea lice. Thus, this research used whole-genome sequencing (WGS) to study the genetic basis of the trait since most research using fewer SNPs did not identify significant quantitative trait loci. MOWI Genetics AS provided the genotype (50k SNPs) and phenotype data for this research after conducting a sea lice challenge test on 3,185 salmon smolts belonging to 191 full-sib families. The 50k SNP genotype was imputed to WGS using the information from 197 closely related individuals with sequencing data. The challenged population's WGS and 50k SNPs were then used to estimate genetic parameters, perform a genome-wide association study (GWAS), predict genomic breeding values, and estimate its accuracy for host resistance to sea lice. The heritability of host resistance to sea lice was estimated to be 0.21 and 0.22, while the accuracy of genomic prediction was estimated to be 0.65 and 0.64 for array and WGS data, respectively. In addition, the association test using both array and WGS data did not identify any marker associated with sea lice resistance at the genome-wide level. We conclude that sea lice resistance is a polygenic trait that is moderately heritable. The genomic predictions using medium-density SNP genotyping array were equally good or better than those based upon WGS data.